2016
DOI: 10.3389/fmicb.2016.00998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Analysis of Streptomyces Species Reveals Their Adaptation to the Marine Environment and Their Diversity at the Genomic Level

Abstract: Over 200 genomes of streptomycete strains that were isolated from various environments are available from the NCBI. However, little is known about the characteristics that are linked to marine adaptation in marine-derived streptomycetes. The particularity and complexity of the marine environment suggest that marine streptomycetes are genetically diverse. Here, we sequenced nine strains from the Streptomyces genus that were isolated from different longitudes, latitudes, and depths of the South China Sea. Then w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 97 publications
(108 reference statements)
1
50
2
1
Order By: Relevance
“…During this process, pan-genome variation, which caused by horizontal transfer (gene gain), gene loss, and duplication, has played a signi cant role, and also enable for all possible lifestyles and an increasing biodiversity [27][28][29]. For example, a population genomics study of the vibrios showed a tremendous pan-genome with substantial gene gain and loss events in the evolutionary history, enabling vibrios occupy various niches [30]; similar phenomena were also shown in streptomycetes, where genome uctuation guarantees the species a quick and economical response to diverse niches of lifestyles [31,32]; a recent study has also shown a rapidly evolved gene repertoire that could enhance the ecological adaptability of Escherichia coli in different environments [33]. The rst complete genome sequence of M. luteus revealed a circular chromosome with one of the smallest genomes of free-living actinobacteria and an abnormally high number of transposable elements [3].…”
Section: Introductionmentioning
confidence: 99%
“…During this process, pan-genome variation, which caused by horizontal transfer (gene gain), gene loss, and duplication, has played a signi cant role, and also enable for all possible lifestyles and an increasing biodiversity [27][28][29]. For example, a population genomics study of the vibrios showed a tremendous pan-genome with substantial gene gain and loss events in the evolutionary history, enabling vibrios occupy various niches [30]; similar phenomena were also shown in streptomycetes, where genome uctuation guarantees the species a quick and economical response to diverse niches of lifestyles [31,32]; a recent study has also shown a rapidly evolved gene repertoire that could enhance the ecological adaptability of Escherichia coli in different environments [33]. The rst complete genome sequence of M. luteus revealed a circular chromosome with one of the smallest genomes of free-living actinobacteria and an abnormally high number of transposable elements [3].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes, the scale of which far outstrips that of base-by-base mutation, enable bacteria to quickly respond to environmental changes and to exploit new ecological niches [4345]. With regard to bacteria such as B .…”
Section: Discussionmentioning
confidence: 99%
“…The core genome is the common set of shared genes among all testing strains, the pan-genome is the entire set of genes within test genomes, the accessory genome is the set of genes shared with more than two but not all testing strains and unique genes is the set of genes in each strain not shared with other strains [27]. The details of the strains used were listed in Table 2.…”
Section: Comparative Genomics Analysismentioning
confidence: 99%